Quantifying the contribution of mangroves to local fish consumption in Indonesia: a cross-sectional spatial analysis - Amy Ickowitz, PhD; Michaela Guo Ying Lo, MSc; Mulia Nurhasan, PhD; Agus Muhamad Maulana, BSc; Benjamin Michael Brown, PhD (The Lancet Planetary Health, 2023)
Summary: Background: Indonesia has lost more mangroves than any other country. The importance of mangroves for carbon storage and biodiversity is well recognised, but much less is known about what they contribute to the communities living near them who are called on to protect them. Malnutrition in Indonesia is high, with more than a third of children stunted, partly due to poor diets. Fish are nutrient-rich and are the most widely consumed animal source food in Indonesia, making the relationship between mangroves and fish consumption of great importance. Aquaculture is also tremendously important for fish production in Indonesia and has replaced large areas of mangroves over the last two decades. Methods: We performed a cross-sectional, spatial analysis in this study. We combined data on fish consumption for rural Indonesian coastal households from the Indonesian National Socioeconomic Survey with spatial data on mangrove forest and aquaculture area from the Indonesian Ministry of Environment and Forestry to create a cross-sectional spatial dataset. Using a mixed-effects regression model, we estimated to what extent living in proximity to different densities of mangroves and aquaculture was associated with fresh fish consumption for rural coastal households. Findings: Our sample included 6741 villages with 107 486 households in 2008. The results showed that rural coastal households residing near high-density mangroves consumed 28% (134/477) more fresh fish and other aquatic animals, and those residing near medium-density mangroves consumed 19% (90/477) more fresh fish and other aquatic animals, than coastal households who did not live near mangroves. Coastal households that lived near high-density aquaculture consumed 2% (9/536) more fresh fish, and those that lived near medium-density aquaculture consumed 1% (3/536) less, than other rural coastal households. Interpretation: Mangroves contribute substantially to the food security and nutrition of coastal communities in Indonesia. This finding means that the conservation of mangroves is important not only for carbon storage and biodiversity, but also for the communities living near them. Aquaculture does not appear to offer similar food security benefits. Funding: Bureau for Economic Growth, Education, and Environment, United States Agency for International Development.